Solar Intensity X-Ray and Particle Spectrometer SIXS: Instrument Design and First Results - Huovelin J; Vainio R; Kilpua E; Lehtolainen A; Korpela S; Esko E; Muinonen K; Bunce E; Martindale A; Grande M; Andersson H; Nenonen S; et al. (SPRINGER, 2022)
The Solar Intensity X-ray and particle Spectrometer (SIXS) on the BepiColombo Mercury Planetary Orbiter ("Bepi") measures the direct solar X-rays, energetic protons, and electrons that bombard, and interact with, the Hermean surface. The interactions result in X-ray fluorescence and scattering, and particle induced X-ray emission (PIXE), i.e. "glow" of the surface in X-rays. Simultaneous monitoring of the incident and emitted radiation enables derivation of the abundances of some chemical elements and scattering properties of the outermost surface layer of the planet, and it may reveal other sources of X-ray emission, due to, for example, weak aurora-like phenomena in Mercury's exosphere. Mapping of the Hermean X-ray emission is the main task of the MIXS instrument onboard BepiColombo. SIXS data will also be used for investigations of the solar X-ray corona and solar energetic particles (SEP), both in the cruise phase and the passes of the Earth, Venus and Mercury before the arrival at Mercury's orbit, and the final science phase at Mercury's orbit. These observations provide the first-ever opportunity for in-situ measurements of the propagation of SEPs, their interactions with the interplanetary magnetic field, and space weather phenomena in multiple locations throughout the inner solar system far away from the Earth, and more extensively at Mercury's orbit. In this paper we describe the scientific objectives, design and calibrations, operational principles, and scientific performance of the final SIXS instrument launched to the mission to planet Mercury onboard BepiColombo. We also provide the first analysis results of science observations with SIXS, that were made during the Near-Earth Commissioning Phase and early cruise phase operations in 2018-19, including the background X-ray sky observations and "first light" observations of the Sun with the SIXS X-ray detection system (SIXS-X), and in-situ energetic electron and proton observations with the SIXS Particle detection system (SIXS-P).